Incidence of Accidental Poisoning by Common Household Substances - Yousaf, Muhammad; Ansari, Rizwan Zafar; Ahmed, Anwar; Khalil, Zahid Hussain (International Journal of Pathology, 2018)
Objective: To determine common household poisonous substances and trend of poisoning in terms of nature of poisoning, clinical manifestation and victims age group.Methods: A retrospective study was conducted at major tertiary care hospitals of Rawalpindi including Holy Family Hospital, Civil Hospital and Benazir Hospital (former RGH). Data was collected from the medico-legal clinics and record room of hospital emergency and autopsy centers. The data was collected from January 2008 to December 2017. All cases of poisoning were collected; socioeconomic status, age, sex and other demographic details were analyzed along with frequency of commonly used substances and their clinical presentation by using SPSS 19. Mean and standard deviation was calculated for quantitative variables, like age, time passed since exposure to poison. Frequency and percentages were calculated for qualitative data including factors leading to accidental poisoning.Results: During the period of 10 years, 2627 were cases of poisoning reported in causality department of tertiary care hospitals of district Rawalpindi. Of them, medical records of 2303(87.6%) cases were reviewed; 542(23.5%) adult due to accidental intake and 1761(76.4%) pediatric cases below 16 years of age most common cause was accidental intake of chemicals placed in incanting colored rapper bottles placed in approachable areas. In 324(12.3%) cases, the poisoning occurred due to animal bite. Psychiatric drug over dose was found in 667(29%) cases, followed by prescription drugs 561(24.4%), pesticides 35.2(15.3%), hydrocarbons 23.0(10%), analgesics 20.0(8.7%), household toxins 20.0(8.7%), alcohol, drug abuse 68(2.97%) and others 153(6.67%). Exclusion criteria was poisoning outside home and animal bite.Conclusion: Poisoning was a serious cause of morbidity in children and young adults. Easy accesses to medications were the leading cause and home was the most common place of incident